Thermal quench and current profile relaxation dynamics in massive-material-injection-triggered tokamak disruptions. (23rd September 2021) - Nardon, E; Hu, D; Artola, F J; Bonfiglio, D; Hoelzl, M; Boboc, A; Carvalho, P; Gerasimov, S; Huijsmans, G; Mitterauer, V; Schwarz, N; Sun, H
Abstract: 3D non-linear magnetohydrodynamic simulations of a disruption triggered by a massive injection of argon gas in JET are performed with the JOREK code. The key role of the thermal drive of the m  = 2, n  = 1 tearing mode (i.e. the drive from helical cooling inside the island) in the disruption process is highlighted by varying the amplitude and position of the argon source across simulations, and also during a simulation. In cases where this drive persists in spite of the development of magnetic stochasticity, which is favoured by moving the argon source in an ad hoc way from the plasma edge into the 2/1 island at some point in the simulation, a relaxation in the region q ⩽ 2 (roughly) takes place. This relaxation generates a plasma current spike comparable to the experimental one. Simulations are compared in detail to measurements via synthetic diagnostics, validating the model to some degree.